Single-Stage Orbital Socket Reconstruction Using the Oversized Dermis Fat Graft and the 22 mm Silicone Orbital Implant after an Extended Enucleation - Biljana Kuzmanović Elabjer; Mladen Bušić; Daliborka Miletić; Mirjana Bjeloš; Borna Šarić; Damir Bosnar (Case Reports in Ophthalmological Medicine)
We would like to present a surgical technique of orbital socket reconstruction using oversized dermis fat graft and 22 mm silicone orbital implant in a single-stage after extended enucleation in two patients with massive local recurrence of anteriorly located choroidal melanoma previously treated with endoresection. Orbital tissues en bloc were removed leaving conjunctival lining only at the fornices. Simultaneously, the 22 mm silicone sphere was implanted deeply into the orbit and covered with the oversized dermis fat graft of 30 mm in height and 35 mm in length with 20 mm of the fat thickness. The graft was sutured to the residual forniceal conjunctiva with interrupted 6/0 absorbable sutures overlapping conjunctiva with the graft edge for 2 mm to facilitate the epithelization. Epithelization was completed in two months, leaving well-formed fornices with good fitting of the prosthesis. The key point of orbital socket reconstruction after extended enucleation is to restore conjunctival lining prior to volume. Thus, whenever facing a massive volume and conjunctival lining loss, simultaneous insertion of the 22 mm silicone sphere deep into the orbit combined with oversized dermis fat graft is, in our opinion, the method of choice. It proved to be safe and effective with favourable long-term results.